Intimate metropolis [ urban subjects in the modern city - Di Palma, Vittoria; Lathouri, Marina; Periton, Diana (Routledge, 2009)
Questions traditional conceptualizations of 'public' and 'private, ' and illuminates the ways in which the modern metropolis can be seen as a peculiarly intimate construction, with its notion of the public predicated ultimately on a concept of the private individual or autonomous self